PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE DIPADU PROBLEM BASED LEARNING UNTUK MENINGKATKAN PARTISIPASI DAN PEMAHAMAN KONSEP SISWA - Dian, Elsy; Sunarmi, Sunarmi; Suhadi, Suhadi (Jurnal Pendidikan Biologi, 2016)
Result of observations and teacher interviews class of natural sciences VIII-H Junior High School 20 Malang, information obtained student participation in learning activities is low. Evident from; (1) The classical completeness third aspect of student participation that aspect of the task, the business discussion, and the liveliness of the opinion reached only 12.5% of 32 students and understanding the concept of students is low as evidenced by the results of tests on classical completeness system material only amounted to 37.5%. (2) understanding the concept of students is low as evidenced by the results of tests on classical completeness system material only amounted to 37.5%. The solution can be applied is the application of PBL learning model TPS combined. This research was conducted in classes VIII-H Junior High School 20 Malang, the second semester 2015/2016. Data taken in this study is enforceability of TPS combined PBL learning, student participation, and students' understanding of the concept. The results showed that the learning model of TPS combined PBL can improve students' participation and understanding of the concept.